Policy Mix, Public Debt Management and Fiscal Rules : Lessons from the 2002 Brazilian Crisis - Herrera, Santiago (World Bank, Washington, DC, 2012)
Despite significant progress in economic reform throughout the 1990s, and an exemplary development of the policymaking framework in the second part of the decade, Brazil suffered a major public debt and currency crisis in 2002. Though the political origin of the uncertainty cannot be ignored, the author identifies other sources of uncertainty emanating from the policymaking framework: fiscal policy was not responsive to the shocks, public debt instruments were used with several objectives (to stabilize the currency and to lengthen maturity) and there was inadequate supervision of agents holding public debt. Most of the flaws have been fixed following the crisis: a) The primary fiscal balance has been increased, sending the signal that it is a flexible instrument that will be used to ensure commitment of the sovereign to honor its obligations. b) The central bank formally transferred to the Treasury the remaining debt-issuance functions, facilitating a more adequate balancing of different risks involved in debt management. c) Mutual funds' public debt holdings are better regulated, ensuring that end-investors have the proper information to assess the risk of the institutions in which they invest.